Correlation of sleep quality and cardiac autonomic modulation in hemodialysis patients - Carneiro, Erika Ribeiro; Azoubel, Luana Anaisse; Dias, Raimunda Carneiro; Dias, Carlos José; Sá, Emanuelle Sousa; Brito, Dyego Araujo; Salgado Filho, Natalino; Santos, Elton Freitas; Rocco, José Hermógenes; Mostarda, Cristiano Teixeira; Bernardo Filho, Mario (Sleep Science, 2022)
Objectives Sleep disorders in patients on hemodialysis are frequent, but few studies correlate these disorders with autonomic dysfunction in these patients. This study aimed to verify whether clinical and laboratory variables and heart rate variability are associated with worse sleep quality verified by the Pittsburg subjective scale in patients on hemodialysis.Material and Methods A cross-sectional study was performed on forty-eight patients. Epidemiological, clinical, and laboratory data were collected. After were performed by recording the heart rate variability and applied Pittsburg questionnaires, Beck anxiety index (BAI), and Beck depression index (BDI). The global PSQI score >5 indicates that a person is a poor sleeper, the patients were divided according to the scores in the Pittsburg questionnaire into good and poor sleepers and the differences between all variables were analyzed.Results Forty-eight patients were evaluated and the prevalence of 68.7% (n=33) of poor sleep quality was verified. From the depression and anxiety questionnaires, it was found that only 18.7% (n=9) had criteria for depression. In the analysis of the sympathetic dysfunction parameters, it was found that in the group with good sleep quality in the frequency domain (HFm2) and the LFnu in the group with worse sleep quality. There was a positive correlation between sleep quality scores the anxiety and depression scores. It is also verified that the variables LFnu had a positive correlation with higher scores of quality of sleep and HFnu had a negative correlation with the highest scores of quality of sleep.Conclusion In patients undergoing hemodialysis, the poorest quality of sleep is correlated with worse cardiac autonomic modulation as well as higher scores on the depression and anxiety scales.
Keywords: Sleep Quality; Hemodialysis; Autonomic Nervous System Diseases